Temporal Changes in Bacterial Profile of Burn Wound Infections in a Tertiary Care Hospital and Risk Factors for Invasion: A Prospective Cohort Study - Aarti A Gandhi; Priyanka S Prasad; Gita Nataraj; Vinita Puri (Journal of Clinical and Diagnostic Research)
Introduction: Burn wound infections remain a significant cause of morbidity and mortality in patients admitted to burn units. Burn wounds serve as a susceptible site for opportunistic colonisation by endogenous and exogenous organisms due to local and systemic immunosuppression. The bacterial infection profile changes over time in hospitalised patients which increases the risk of systemic invasion. Aim: To determine the temporal changes in the bacterial profile of burn wound infections and identify the risk factors associated with invasive infections. Materials and Methods: A prospective cohort study of patients with burn injuries was conducted over 15 months in the burns unit of a tertiary care hospital in Mumbai, Maharashtra, India. Since, it was a time bound prospective cohort study, samples from all patients admitted with burn wounds between June, 2018 and September, 2019 were considered as study participants (n=131). Wound swabs were obtained from patients upon admission and subsequently at regular intervals. Bacterial isolates were identified and their antibiotic susceptibility patterns were determined. Data were analysed to identify temporal changes in the bacterial profile to determine the risk factors associated with invasive infections. Results: A total, of 131 patients with burn injuries were included. A total of 503 swabs were collected, of which 373 (74.2%) showed bacterial growth; five (1.34%) were contaminants and were excluded from analysis. Gram-negative bacteria were the predominant isolates in the first week, whereas gram-positive organisms predominated from the second week onwards. The most common organism isolated was Pseudomonas aeruginosa (n= 100, 27.17%) followed by Staphylococcus aureus (n=84, 22.83%), Acinetobacter baumannii (n=74, 20.11%), and Klebsiella pneumoniae (n=65, 17.66%). A total of 74 blood culture specimens were collected from 47 patients suspected of having invasive infections based on clinical signs and symptoms of systemic infection clinically. Of these, 37 patients (78.7%) were culture positive. Mortality was noted in 28 patients (28/31, 90.32%) in the group with invasive infections. Upon calculating the Odds Ratio (OR), risk factors found to be associated with invasive infections included a higher degree and depth of burns and a longer hospital stay. Conclusion: The shift from gram-negative to gram-positive bacteria and the increasing resistance over time highlight the importance of ongoing surveillance and appropriate antimicrobial stewardship measures in the management of burn wound infections.